2016
DOI: 10.1080/13557858.2016.1263287
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in risk factors of acute pancreatitis

Abstract: Taiwanese aborigines were reported to be more susceptible to alcohol-related pancreatitis than nonaborigines. The decreasing levels of excessive alcohol consumption may reduce the disease burden of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Although the previous studies have demonstrated male predominance in the NAFLD population, the exact mechanism is not comprehensively understood (6). However, the present retrospective study discovered that the prevalence of NAFLD in women was higher than that in men, which can be possibly explained by the fact that women have a higher percentage of essential body fat, or by the tendency of men to consume more alcohol (17), which in turn can result in alcoholic hepatitis -and that was an exclusion criterion in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Although the previous studies have demonstrated male predominance in the NAFLD population, the exact mechanism is not comprehensively understood (6). However, the present retrospective study discovered that the prevalence of NAFLD in women was higher than that in men, which can be possibly explained by the fact that women have a higher percentage of essential body fat, or by the tendency of men to consume more alcohol (17), which in turn can result in alcoholic hepatitis -and that was an exclusion criterion in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Different studies have documented the prognosis of acute pancreatitis patients in relation to underlying etiological factors; every study has shown different statistics in their region. 8,9 Developed countries like USA, UK, Japan, and china where alcohol consumption is higher than the developing countries are also linked to higher mortality rates in alcohol associated pancreatitis because chronic consumption of alcohol predispose the patients with liver cirrhosis and pancreatitis which affects the outcome in these patients and leads to poor prognosi. On the other hand, some of the studies also observed that pancreatitis caused by gallstones has more severe and insidious onset and is associated with higher mortality than alcohol induced AP.…”
Section: Introductionmentioning
confidence: 99%